KAJIAN AYAT-AYAT TEOLOGIS DALAM TAFSIR AL IBRIZ KARYA KH. BISRI MUSTOFA - Mu'jizat, Lailatul (Jurnal Al-Dirayah, 2019)
This article aims to discuss the interpretation of a few Qur?anic verses of Tafsir Al Ibriz,  written by KH Bisri Mustofa, that contain theological teachings. From literature study it was known that KH Bisri Mustafa used bi al-ra?yi approach, as well as bi al-ma?tsur, i.e. using hadith to strengthen the intepretation of the verse. His theology is influenced by Maturidiah and Mu?tazilah, with a tasawuf style. While in terms of method, he used ijmali which tend to be short in explaining the meaning of the verse.